Frequency of Visceral Injury and Post-Operative Port Site Hernia from Direct Trocar Insertion for Gaining Access to Peritoneal Cavity in Laparoscopic Cholecystectomy - Khan, Nadir Saifullah; Shahzad, Talat; Naz, Saman; Khan, Ulas; Saleem, Mohammad; Khan, Haris Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To see the frequency of visceral injury and port site hernia from direct trocar entry in laparoscopic cholecystectomy. Study Design: Place and Duration of Study: Department of Surgery, District Headquarters Teaching Hospital Abbottabad from 1st December 2017 to 20th September 2019. Methodology: Two hundred and sixty patients requiring laparoscopic cholecystectomy were enrolled. Direct trocar technique was used for peritoneal first port entry using retractable trocar in all patients. Demographic characteristics of the patients, as well as intraoperative visceral injury and post operative port site hernia formation were recorded. Results: Majority of study participants were females: 229 (88 %) women while remaining men. Mean age of study population was recorded as 37±8 years. Females were older than males (p > 0.05).We have not seen a single case of visceral injury or hernia formation in our study. Conclusions: The blind technique with retractable port is safe for first port entry into peritoneum in terms of visceral injury and also hernia formation.